Excellent beauty the naturalness of religion and the unnaturalness of the world - Dietrich, Eric (New York Chichester Columbia University Press, 2015)
Eric Dietrich is professor of philosophy at Binghamton University and the founding editor and current editor in chief of the Journal of Experimental and Theoretical Artificial Intelligence. He is the author of numerous papers and several books focusing on cognitive science, consciousness, artificial intelligence, metaphysics, epistemology, and philosophy of mind.
The traveler to excellent beauty : invited rather than draftedOf spiritual journeys--What is a religion? -- The one billion -- The traveler's dark night of the soul -- Appendix to chapter 4. Statistics and probability meet job -- The biology of religion, the psychology of morality -- Justifying the ways of God to man .. via evolution -- Appendix to chapter 5. Yes, there really is such a thing as a coincidence -- Does God want you dead? -- Good without gods -- The journey in tatters -- Beyond atheism : the religion illusion -- The Janus-faced hominid -- The heretic's way : into the mysterious realm -- Some strangeness in the proportion -- Appendix to chapter 10. A compendium of mysteries -- The beauty of seeing more than we can understand -- Appendix to chapter 11. Welcome to the inscrutable -- The personal mystery and the impersonal God -- Summa mysteriologica.
Literaturverzeichnis: Seite 183-187
Keywords: Natural Theology